Clinical management and disease-modifying treatment for amyotrophic lateral sclerosis in African hospital centers: the TROPALS study. Issue 3 (3rd April 2022) - Luna, Jaime; Jost, Jeremy; Diagana, Mouhamadou; Ait Aissa, Leila; Tazir, Meriem; Ali Pacha, Lamia; Kacem, Imen; Gouider, Riadh; Henning, Franclo; Basse, Anna; Cisse, Ousmane; Balogou, AA Koffi; et al.
Abstract: Objective: To assess the availability of health workers and medications for clinical management of amyotrophic lateral sclerosis (ALS) in African hospital centers. Availability and affordability analyses of disease-modifying treatments were performed. Methods : A multicenter observational study involving African hospitals was conducted. A standard questionnaire was developed based on the European Federation of the Neurological Societies (EFNS) guidelines. We collected data on multidisciplinary care and availability of medicines. The availability and affordability were evaluated according to the WHO guidelines. Results : Nine hospital centers from eight African countries participated. We observed a low degree of implementation of multidisciplinary care in ALS management. Riluzole was only available in centers from South Africa, Senegal, Tunisia, and Togo. This treatment was unaffordable and the adjusted price was highly variable among countries. The cost of riluzole was partly or fully covered by patients, which implies a substantial economic burden. Conclusion : Our findings strengthen the need to promote multidisciplinary care in the clinical management of ALS in Africa. Disease-modifying medication should be both available and affordable. Local and international collaboration is needed to improve ALS health care access in Africa.